Combined Plyometric and Short Sprint Training in U-15 Male Soccer Players: Effects on Measures of Jump, Speed, Change of Direction, Repeated Sprint, and Balance - Aloui, Ghaith; Hermassi, Souhail; Bartels, Thomas; Hayes, Lawrence D.; Bouhafs, El Ghali; Chelly, Mohamed Souhaiel; Schwesig, René (Frontiers in Physiology, 2022)
This study examined the effect of 8 weeks of biweekly combined plyometric and short sprint training into the typical within-season training schedule of youth male soccer players. Participants were allocated at random to an experimental group (EG; n = 17, age: 14.6 ± 0.5 years, body mass: 60.5 ± 7.1 kg, height: 1.64 ± 0.08 m, body fat: 11.3 ± 1.4%) and a control group (CG; n = 17, age: 14.6 ± 0.4 years, body mass: 61.0 ± 3.9 kg, height: 1.67 ± 0.05 m, body fat: 11.8 ± 1.4%). Measures obtained pre- and post-intervention included vertical and horizontal jump performances (i.e., squat jump (SJ), countermovement jump with aimed arms (CMJA), and five-jump test (FJT)) and sprint performances (i.e., 10 and 30 m sprint). In addition, change-of-direction ability (sprint with 90° Turns (S90°) and sprint 9–3–6–3–9 m with backward and forward running (SBF)), repeated shuttle sprint ability (RSSA), and dynamic balance performance (Y balance test) were measured pre- and post-intervention. The EG experienced higher jump (all p < 0.05; d ≥ 0.71), sprint (all p < 0.05; d ≥ 0.64), change-of-direction ability (all p < 0.05; d ≥ 0.66), RSSA (all parameters except the fatigue index p < 0.01; d ≥ 0.71), and dynamic balance (all p ≤ 0.05; d ≥ 0.50) improvement compared to the CG. Adding biweekly combined plyometric and short sprint training to standard training improves the athletic performance of youth male soccer players (under 15 (U15)).